(3QSGdI aj GdeYGOs - (3GdbhGei, GdTjQGRj, UOQ GdOjf, eMeO Hf EHQGgje Hf jMji, J (B1050(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO def efg GdHOGjI hEdjg (B... (3hGdUdGI Ydi ef GJUdJ Hg OGFQI GdhLhO(B...s
(3BNQgG (B:s
...(3eef SHbfG nef Mbb gPg GdeSCdI hCMce bhGfjfgG Ydi gPG GdfMh(B...s
(3JHUQI GdeDda (B:s
(3CQN UGMH GdCYdGe dhaGJg SfI(B: 1059(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B31s
(3GdCYdGe(B:(3L(B5(3,U(B303s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds